Hydrogels with intrinsic antibacterial activity prepared from naphthyl anthranilamide (NaA) capped peptide mimics - Aldilla, Vina R.; Chen, Renxun; Kuppusamy, Rajesh; Chakraborty, Sudip; Willcox, Mark D. P.; Black, David StC; Thordarson, Pall; Martin, Adam D.; Kumar, Naresh (Scientific reports, 2022)
In this study, we prepared antibacterial hydrogels through the self-assembly of naphthyl anthranilamide (NaA) capped amino acid based cationic peptide mimics. These ultra-short cationic peptide mimics were rationally designed with NaA as a capping group, l -phenylalanine, a short aliphatic linker, and a cationic group. The synthesized peptide mimics efficiently formed hydrogels with minimum gel concentrations between 0.1 and 0.3%w/v. The resulting hydrogels exhibited desirable viscoelastic properties which can be tuned by varying the cationic group, electronegative substituent, or counter anion. Importantly, nanofibers from the NaA-capped cationic hydrogels were found to be the source of hydrogels’ potent bacteriacidal actvity against both Gram-positive and Gram-negative bacteria while remaining non-cytotoxic. These intrinsically antibacterial hydrogels are ideal candidates for further development in applications where bacterial contamination is problematic.